2022
DOI: 10.1038/s41388-022-02386-8
|View full text |Cite
|
Sign up to set email alerts
|

CircME1 promotes aerobic glycolysis and sunitinib resistance of clear cell renal cell carcinoma through cis-regulation of ME1

Abstract: Circular RNAs (circRNAs) play critical roles in clear cell renal cell carcinoma (ccRCC). However, their involvement in sunitinib resistance remains largely unknown. Herein, we identified a novel circRNA, named circME1, which contributes to sunitinib resistance development in ccRCC. CircME1 also promoted proliferation, migration, and invasion of ccRCC cells. Further mechanism analysis showed that circME1 interacted with U1 snRNP at the promoter of its parental gene ME1, thereby upregulating the expression of ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…It is promising to be a new prognostic indicator and a promising therapeutic target. CircME1 interacts with U1 snRNP to upregulate ME1 expression and thereby promote resistance to sunitinib in renal cancer cells [ 201 ]. The study suggests that circME1 may be a promising biomarker for predicting sunitinib resistance and a therapeutic target for ccRCC.…”
Section: Circrnas Are Potential Diagnostic and Prognostic Biomarkers ...mentioning
confidence: 99%
“…It is promising to be a new prognostic indicator and a promising therapeutic target. CircME1 interacts with U1 snRNP to upregulate ME1 expression and thereby promote resistance to sunitinib in renal cancer cells [ 201 ]. The study suggests that circME1 may be a promising biomarker for predicting sunitinib resistance and a therapeutic target for ccRCC.…”
Section: Circrnas Are Potential Diagnostic and Prognostic Biomarkers ...mentioning
confidence: 99%
“…Recent studies have reported the role of circRNA in ccRCC. For example, Gui et al ( 27 ) reported that circCHST15 promotes ccRCC cell proliferation and metastasis through the miR-125a-5p/EIF4EBP1 axis, Zhang et al ( 28 ) proposed the circME1/ME1 pathway as involved in ccRCC progression and sunitinib resistance development ( 29 ) and Wang et al ( 29 ) presented circDVL1 as exerting a tumor-suppressive function during ccRCC progression through the circDVL1/miR-412-3p/PCDH7 axis. The upregulation of circWWC3 expression was observed in ccRCC tissues in the present study, and patients with high circWWC3 expression levels exhibited worse overall survival OS times.…”
Section: Discussionmentioning
confidence: 99%
“…EIciRNAs such as CircEIF3J and CircPAIP2, which are also present in the nucleus, bind to the U-small ribonucleoprotein and then to pol II to similarly regulate gene expression (18). Additionally, many studies have shown that ciRNAs and EIciRNAs may have cisregulatory effects on the transcription of the coding gene (19).…”
Section: Transcriptional Regulationmentioning
confidence: 99%